Sosialisasi dan Peningkatan Pengetahuan Manajemen Keuangan pada Siswa Rumah Yatim dan Pesantren Ruhama - Neneng Khoiriah; Cristine Prestarika Lukito; Hasanudin Hasanudin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Financial literacy is an essential life skill for students because daily decisions about pocket money, spending priorities, saving, and future goals shape their financial habits. This community service activity aimed to improve students' understanding of the value of money, personal budgeting, the distinction between needs and wants, saving behavior, and short- and long-term financial planning at the Ruhama Orphanage and Islamic Boarding School in Gunung Sindur, Bogor. The program was conducted on 3-5 November 2025 through lectures, interactive question-and-answer sessions, simple budgeting simulations, discussions, and end-of-activity evaluation. The implementation report recorded the participation of 35 students. The activities received positive support from the institution, and participants showed high enthusiasm during the delivery of materials and practical exercises. Observations during the program indicated that several students had begun to understand basic financial management, while others still required guidance in calculating expenses, recording cash flows, and preparing detailed budgets. The program encouraged participants to review excessive spending habits, prioritize essential needs, commit to regular saving, and formulate short-term financial goals. The findings imply that contextual and interactive financial education is relevant for adolescents, but continued practice and support from teachers and caregivers are needed to transform knowledge into consistent financial behavior.